(untitled) (Research, Society and Development, 2022)
Objective: To analyze the percentage of obese people and the level of physical activity in university students in the border region. Method: Academic and cross-sectional study, in which university students from the border region of the city of Foz do Iguaçu-PR. A data search was carried out on the body weight index, for the diagnosis of obesity, where the search format of international physical activity, online version that evaluated the level of physical activity, was not applied. Results: it was possible to find 62 university students who are 20.8% and 37 are in contact with obesity, corresponding to 17.8% of university students. With regard to the level of physical activity of the students in this study, very similar results are presented in relation to the Active and Active categories, 25.0% respectively, and in relation to BMI, 48.1% were considered in relation to the mass index. normal body, which is considered a positive result. Conclusion: Based on the results, it is possible to infer that the percentage of obese people at the border who responded to the region is lower than similar studies. This may have occurred due to the approach due to the pandemic - online form - self-report and or is really a characteristic of the population addressed.